The Influence of Narcissistic Personality Tendencies on Self-Disclosure in Social Media - Natasya Pustika Siregar; Siti Nuzulia (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Social media has become an important platform for individuals to disclose personal information online, which can be associated by personality factors such as narcissistic personality tendencies. This tendency has several dimensions, including exhibitionism, self-sufficiency, exploitativeness, entitlement, superiority, and authority. This study aims to examine the influence of each of these narcissistic traits on self-disclosure on social media and to test whether gender influences these relationships. A cross-sectional study involved 266 Indonesian young adults aged twenty to twenty-nine years. Participants completed questionnaires measuring the Narcissistic Personality Inventory (NPI-40) and a modified version of the Revised Self-Disclosure Scale (RSDS). The results showed that exhibitionism, entitlement, and self-sufficiency positively influenced self-disclosure on social media. In contrast, superiority, authority, and exploitativeness did not show significant effects. Additionally, the pattern of relationships was similar for both males and females, indicating that gender did not influence narcissistic tendencies on self-disclosure. This study contributes to exploring every narcissistic dimension in a collectivist cultural context. Then, the findings provide an understanding of how personality shapes online behavior and offer insights for future cross-cultural psychological research.